Home automation control system using Arduino: article / Mustaffa Ibrahim - Ibrahim, Arduino Mustaffa (2012)
Energy saving is an important issue in the times of increasing energy prices. Products and services provided by the information and communication technology (ICT) can support energy efficiency and emissions reductions. The synergy of ICT and a residential area gives rise to the home automation control system environment. Ecological and home automation control system network applications could improve the peoples life satisfaction in the domain of health care, security protection, and efficient management of energy and resource consumption. A home automation control system in the smart grid is the latest addition to a family of ideas emerging in relation to the ICT usage in the home. This paper presents an overview of the home automation control system concept and some challenges that ICT faces in that environment. A home automation control system is a residence equipped with technology that could observes the residents and provides proactive services. With the availability of inexpensive low-power sensors, radios, and embedded processors, current home automation control system are typically equipped with a large amount of networked sensors which collaboratively process and make deductions from the acquired data on the state of the home as well as the activities and behaviors of its residents.